Antimicrobial activity of biogenically produced spherical Se‐nanomaterials embedded in organic material against Pseudomonas aeruginosa and Staphylococcus aureus strains on hydroxyapatite‐coated surfaces. Issue 4 (23rd February 2017) - Piacenza, Elena; Presentato, Alessandro; Zonaro, Emanuele; Lemire, Joseph A.; Demeter, Marc; Vallini, Giovanni; Turner, Raymond J.; Lampis, Silvia
Summary: In an effort to prevent the formation of pathogenic biofilms on hydroxyapatite (HA)‐based clinical devices and surfaces, we present a study evaluating the antimicrobial efficacy ofS pherical biogenic Se‐N anostructuresEm bedded inO rganic material (Bio Se‐NEMO‐S) produced by Bacillus mycoides SelTE01 in comparison with two different chemical selenium nanoparticle (SeNP) classes. These nanomaterials have been studied as potential antimicrobials for eradication of established HA‐grown biofilms, for preventing biofilm formation on HA‐coated surfaces and for inhibition of planktonic cell growth of Pseudomonas aeruginosa NCTC 12934 and Staphylococcus aureus ATCC 25923. Bio Se‐NEMO resulted more efficacious than those chemically produced in all tested scenarios. Bio Se‐NEMO produced by B. mycoides SelTE01 after 6 or 24 h of Na2 SeO3 exposure show the same effective antibiofilm activity towards both P. aeruginosa and S. aureus strains at 0.078 mg ml −1 (Bio Se‐NEMO6 ) and 0.3125 mg ml −1 (Bio Se‐NEMO24 ). Meanwhile, chemically synthesized SeNPs at the highest tested concentration (2.5 mg ml −1 ) have moderate antimicrobial activity. The confocal laser scanning micrographs demonstrate that the majority of the P. aeruginosa and S. aureus cells exposed to biogenic SeNPs within the biofilm are killed or eradicated. Bio Se‐NEMO therefore displayed good antimicrobial activity towards HA‐grown biofilms and planktonic cells, becoming possible candidates as new antimicrobials. Abstract : The prevention of pathogenic biofilms on hydroxyapatite‐based devices formation was studied using either Spherical biogenic Selenium Nanostructures Embedded in Organic material produced by Bacillus mycoides SelTE01 or chemical selenium nanoparticles. Biogenic Selenium Nanostructures Embedded in Organic material resulted more efficacious than those chemically produced in all tested scenarios, becoming possible candidates as new antimicrobials.